Deflationary shocks and monetary rules: An open-economy scenario analysis - Douglas Laxton; Papa N'Diaye; Paolo Pesenti (Federal Reserve Bank of New York, 2006)
The paper considers the macroeconomic transmission of demand and supply shocks in an open economy under alternative assumptions about whether the zero interest rate floor (ZIF) is binding. It uses a two-country general-equilibrium simulation model calibrated to the Japanese economy relative to the rest of the world. Negative demand shocks have more prolonged and conspicuous effects on the economy when the ZIF is binding than when it is not binding. Positive supply shocks can actually extend the period of time over which the ZIF may be expected to bind. Economies that are more open hit the ZIF for a shorter period of time, and with less harmful effects. The implications of deflationary supply shocks depend on whether the shocks are concentrated in the tradables or the nontradables sector. Price-level-path targeting rules are likely to provide better guidelines for monetary policy in a deflationary environment, and have desirable properties in normal times when the ZIF is not binding.
Keywords: E17; E52; F41; 330; deflation; monetary policy rules; zero interest rate floor; Deflation; Schock; Geldpolitik; Regelgebundene Politik; Allgemeines Gleichgewicht; Offene Volkswirtschaft; Simulation; Japan